Diffusion Tensor Imaging in Parenchymal Neuro-Behçet's Disease - Gündüz, Tuncay; Server, Sadık; Küçükali, Cem İsmail; Özyurt, Onur; Demir, Gülşen Akman; Kürtüncü, Murat (Noro-Psikiyatri Arsivi, 2024)
Parenchymal Neuro-Behçet's disease (p-NBD) usually presents with a characteristic lesion in the mesodiencephalic region. However, there is a lack of information regarding the axonal integrity of normal-appearing white matter in p-NBD. Diffusion tensor imaging (DTI) is based on the properties of diffusivity and anisotropy that indicate the integrity of axons. The primary objective of the study was to compare p-NBD patients to healthy controls using diffusion tensor magnetic resonance imaging (DTI-MRI). The study enrolled parenchymal p-NBD patients who maintained stable disease status for 12 months. Healthy controls were chosen from a population with a similar age and gender distribution. Axial DTI was acquired using single-shot echo-planar imaging. Group analyses were carried out using the track-based spatial statistics tool of FMRIB software library (FSL). Correlations between DTI parameters and clinical outcomes were analyzed in the patient group. We recruited 12 patients with p-NBD and 12 healthy individuals. We found significant fractional anisotropy (FA), mean diffusivity (MD), and radial diffusivity (RD) differences in the superior longitudinal fasciculus, superior corona radiata, anterior corona radiata, body and genu of the corpus callosum, external capsule, and anterior limb of the internal capsule, mainly in the frontal white matter. Patients with p-NBD exhibit significant DTI alterations in the otherwise normal-appearing frontal association tracts. This study may contribute to a better understanding of the neuropsychological impairment pattern in patients with p-NBD, which is often associated with frontal cognitive networks.